2007
DOI: 10.1093/hmg/ddm194
|View full text |Cite
|
Sign up to set email alerts
|

Association analysis of functional variants of the FcgRIIa and FcgRIIIa genes with type 1 diabetes, celiac disease and rheumatoid arthritis

Abstract: FcgRIIa and FcgRIIIa are potent modulators of the immune system which bind (auto)antibodies and activate immune cells. The FcgRIIa*A519G and FcgRIIIa*A559C functional variants have been associated with several immune-related diseases. We studied FcgRIIa*A519G and FcgRIIIa*A559C SNPs in type 1 diabetes (T1D), celiac disease (CD) and rheumatoid arthritis (RA) patients and controls and included a meta-analysis of all recent studies of FcgRIIIa*A559C and RA. Our cohorts comprised 350 T1D, 519 CD, 639 RA patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 61 publications
3
47
1
Order By: Relevance
“…2 and one by Alizadeh et al,7 reported association between CD and KIAA1109/Tenr/IL2/ IL21 and FcgRIIa, respectively. Both of these studies were based on a case-control approach, and one purpose of our study was to replicate the most associated SNPs from these publications in a family sample using TDT to avoid the possibility of a false positive finding due to population stratification.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…2 and one by Alizadeh et al,7 reported association between CD and KIAA1109/Tenr/IL2/ IL21 and FcgRIIa, respectively. Both of these studies were based on a case-control approach, and one purpose of our study was to replicate the most associated SNPs from these publications in a family sample using TDT to avoid the possibility of a false positive finding due to population stratification.…”
Section: Discussionmentioning
confidence: 95%
“…7 FcgRIIa is a low affinity activating Fcg receptor that binds immune complexes. Ligation of this Fc receptor leads to phagocytosis, dendritic cell maturation, increased stimulation of T cells and enhanced secretion of inflammatory cytokines.…”
Section: à10mentioning
confidence: 99%
See 1 more Smart Citation
“…This study also revealed that FCRGR3A varies in copy numbers, but compared with FCGR3B at a much lower frequency. The FCRGR3A gene was found to be associated with rheumatoid arthritis (RA) [31,32]. In particular, a strong association for RA susceptibility was found for the FCGR3A-FCGR3B NA2 haplotype [33].…”
mentioning
confidence: 99%
“…More recently also non-HLA genes have been linked to RA susceptibility and disease severity. Variants of the activating Fc gamma receptors Fc RIIIa and Fc RIIIb have been associated with RA susceptibility in Europeans, but not in Asians [69,70]. The Fc RIIIa variant is less effective in IC binding, implicating impaired clearance of ICs might play a role in the pathogenesis of RA, similar to SLE [71].…”
Section: Rheumatoid Arthritismentioning
confidence: 99%